Implementation of The UNO Stacko Game to Improve Communication Skills - Wicaksiwi, Anisa Kartika; Rosdiana, Laily (Jurnal Pijar Mipa, 2024)
Communication skills are essential for interacting socially and conveying and receiving learning material well. This research aims to analyze the improvement of communication skills using the application of the UNO Stacko game. This research was conducted at SMP Negeri 56 Surabaya with a sample of 32 students during three meetings. The research method used is descriptive quantitative, and the research design uses a one-shot case study. Samples are carried out by purposive sampling. The data analysis technique used is by using questionnaires and observation. The research results showed increased students' communication skills, as observed from the questionnaires and observations carried out during three meetings. The results of questionnaires and observations are 86.12% and 85.15% in the outstanding category. So, it can be concluded that the UNO Stacko game media can be applied to improve students' communication skills.